Чисельне моделювання процесу вібраційного переміщення зернівки декою з пульсувальним повітряним середовищем - Степаненко, Сергій Петрович; Stepanenko, Serhii; Котов, Борис Іванович; Kotov, Boris; Волик, Дарина; Volyk, Daryna; Мельник, Віталій; Melnyk, Vitaliy (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Сучасне агропромислове виробництво України потребує нових, більш ефективних машин для очищення зернового вороху та фракціонування зерна. Більшість зерноочисних машин, які пропонуються промисловістю, працює на основі зворотно-поступального руху решітних станів. Проте продуктивність таких машин значно нижча порівняно з тими, де під решітний стан подається повітряний потік, а в нашому випадку – пульсувальний повітряний потік. Водночас точна траєкторія руху зернового матеріалу безпроваль-ним решетом залишається недостатньо вивченою. За частот обертання в межах n = 600 об/хв на початковій стадії руху зернини по решету вона спочатку здійснює синусоїдальний рух, який потім переходить у екс-поненціальне підвищення. На основі проведених розрахунків установлено, що за низької частоти обертання час перебування зернового матеріалу на решеті скорочується, а за максимальної – збільшується через малу відстань між вершинами синусоїди, що підвищує імовірність рекомбінації зернівок за висотою шару мате-ріалу на поверхні безпровального решета. Зміна кута нахилу відносно поздовжньої осі решета також сприяє збільшенню пропускної здатності та покращенню якості розподілу зернового матеріалу. /// EN: Modern agro-industrial production in Ukraine requires new, more efficient machines for cleaning grain mixtures and fractionating grain. Most grain cleaning machines offered by the industry operate based on the reciprocating motion of sieve frames. However, the productivity of such machines is significantly lower compared to those that utilize an airflow, particularly a pulsating airflow, beneath the sieve frame. At the same time, the exact trajectory of grain material movement across the air-permeable sieve remains insufficiently studied.To evaluate the performance of a sieve frame executing reciprocating motion with the combined application of a pulsating airflow, a mathe matical model of grain movement across the sieve was developed. Depending on the sieve’s rotational frequency, the trajectory may become eithe r shortened or elongated. At rotational frequencies around n=600 rpm, during the initial stage of grain movement across the sieve, the grain follows a sinusoidal trajectory that transitions into a smooth exponential rise. Based on the calculations performed, it was established that at lower rotational frequencies, the residence time of the grain material on the sieve decreases, while at maximum frequencies, it increases due to the short distance between the cycloidal cycles, the reby raising the probability of grain kernel recombination along the height of the material layer on the air-permeable sieve surface.Additionally, during movement, the orientation of the grain relative to the sieve changes significantly faster when additional working elements, such as perforated ridges, are installed, compared to a purely reciprocating motion. Altering the inclination angle relative to the sieve’s longitudinal axis furthe r contributes to increased throughput capacity and improved grain material distribution quality.
Numerical modeling of the process of vibrational movement of grain on a deck with a pulsating air environment
Keywords: безпровальне решето; зернина; траєкторія; пульсувальне повітряне середовище; після-збиральна обробка; air-permeable sieve; grain kernel; trajectory; pulsating airflow; post-harvest processing